La evolución de la productividad del sector agropecuario colombiano en el marco de la apertura comercial (2018)
In Colombia the agricultural sector has traditionally been one of the main production sectors. However, currently, the Colombian agriculture does not present a remarkable performance against the needs of development, the potentialities of growth and the opportunities offered by the internal and external markets. According to Kalmanovitz and Lopez (2005), the participation of the Colombian agriculture in GDP has fallen more quickly from early 1990s, opening a gap of 2.5 percentage points in comparison with Latin America. In this regard, Sarmiento(2013) ensures that, in a world dominated by subsidies, the increase in productivity and the low elasticity of income have led to the rapid contraction of agriculture. This research aims to examine the impact of the open trade from the beginning of the 1990s on the productivity of the agricultural sector, based on a model of panel data for 19 countries of Latin America, between 1985 and 2013. Similarly, this...